If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2m+2=6m-1
We move all terms to the left:
2m+2-(6m-1)=0
We get rid of parentheses
2m-6m+1+2=0
We add all the numbers together, and all the variables
-4m+3=0
We move all terms containing m to the left, all other terms to the right
-4m=-3
m=-3/-4
m=3/4
| 6-2n=5n-57 | | 41-t=12 | | n^2-25n+150=0 | | -4(2x+11=92 | | 4x+1/4=-31/7 | | 7x+5(x-5)=35 | | 3x2=2+x | | 5m-(4m-1)=-11-2m | | d/4-8=48 | | 14y=10×(y+6) | | -16x^2-26x+12=0 | | x^2+6x+4.5=0 | | 3+3w=-9 | | 2(1/2q+1)=3(2q-1)4+(2q+1) | | 35+(9x-17)=180 | | -3c-9=15 | | 5c+2(c-4)=3c-7 | | 4(-2x+1)+3=23 | | c2=6c | | (×2+3x+1)(x2+3x+3)=-8 | | 14x=10(x+6) | | 3(5-1e)+2=10 | | -3(u+2)=30-30 | | 27=x/6+8 | | 4.x.x+2=192 | | 2(5z)-13+10=5(3+4z) | | 9/x=21/28 | | 4(x+1)=112 | | 4/7u-6=6 | | -33=-8g+7 | | 3r2+14r+16=0 | | (X)(x+7)=170 |